2016
DOI: 10.1590/s0080-623420160000200007
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of life among survivors of bladder cancer and treatments

Abstract: Objective: To interpret the meanings attributed to the experience of bladder cancer among survivors in therapeutic follow-up. Method: Qualitative methodological approach, based on medical anthropology and narrative methodology. After approval by the research ethics committee of a public university hospital, data were collected from January 2014 to February 2015, by means of recorded semi-structured interviews, direct observation and field journal entries on daily immersion with a group of six men and six women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
3
0
2
Order By: Relevance
“…Patients with BC experience chaotic emotional conditions, such as shame, embarrassment, loss, and resignation after surgery. This finding was similar to a study 24 in which BC survivors experienced the persistence and uncertainty of cancer. In this study, there was an intention to commit suicide among people in their 80s, which was similar to a study 13 that identified old age as a suicide risk factor for BC patients.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with BC experience chaotic emotional conditions, such as shame, embarrassment, loss, and resignation after surgery. This finding was similar to a study 24 in which BC survivors experienced the persistence and uncertainty of cancer. In this study, there was an intention to commit suicide among people in their 80s, which was similar to a study 13 that identified old age as a suicide risk factor for BC patients.…”
Section: Discussionsupporting
confidence: 90%
“…El cuidado de enfermería durante el ciclo vital permanece en constante transición entre la asistencia hospitalaria y el enfoque comunitario; actúa en la atención al niño (8,9) y al adolescente (10)(11)(12), a la familia gestante (13)(14)(15), al adulto joven (16,17) y al adulto mayor (18); además, invita a la reexión, madurando en sus procesos de salud-enfermedad y sus diferentes dimensiones con especialidad, cienticidad y humanidad en la intervención de enfermedades crónicas y degenerativas (19), enfermedades catastrócas (20), formas de violencia (21,22) y relación con el medioambiente (23); por tanto, se requiere responder con efectividad para el logro de la calidad de vida y salud.…”
Section: Discussionunclassified
“…[21][22] In the course of illness processes, normality and improvement in health conditions are usually associated with the possibility of carrying out activities of daily living, with a certain degree of autonomy and efficiency. [21][22] In this perspective, we observed that women in this study performed extra-community activities, some with paid work, and others with voluntary religious activities, but always maintaining the roles of wives, mothers and household caretakers. It has been observed that these are still prominent as the main roles of women in the Western Culture, roles which remain strongly highlighted in the verbal reports.…”
Section: Discussionmentioning
confidence: 99%